The Relevance of Curriculum for Building Modeling and Information Design in Response to Business and Industry Needs in the Digital Era - Ningsih, Yullyani Sartika; Rizal, Fahmi; Ashar, Faisal; Giatman, M (JETL (Journal of Education, Teaching and Learning), 2025)
In the era of digital transformation, the construction industry increasingly demands professionals who are proficient in digital tools such as Building Information Modeling (BIM), 3D modeling, and virtual simulations. This study aims to evaluate the relevance of the Building Modeling and Information Design curriculum at SMKN 1 Bengkalis to the current needs of the business and industrial world. A mixed-methods approach was employed, combining document analysis of curriculum components with survey data from industry representatives to assess graduates’ competencies. The results reveal that while core competencies such as 2D drafting and basic 3D modeling are well-covered and highly relevant, there are significant gaps in the areas of digital project management, advanced BIM proficiency, and the use of innovative tools like VR/AR. Employer feedback indicates moderate satisfaction with graduate readiness, especially in innovation, digital literacy, and collaborative skills. Based on these findings, the study recommends curriculum improvements such as the integration of BIM-based learning modules, incorporation of VR/AR tools, increased collaboration with industry, and the offering of professional certifications. These enhancements are expected to better align vocational education with the evolving technological landscape of the construction sector. In conclusion, while the current curriculum provides a solid technical foundation, continuous updates and strategic partnerships with industry are essential to ensure its relevance in the digital era.